Strategi Komunikasi Fundraising Lembaga Filantropi Islam untuk Meningkatkan Pendapatan Zakat Nasional - Mukhyiddin Mukhyiddin; Musyafa' Musyafa' (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2021)
The purpose of this research is to analyze the concept of fundraising communication strategy or Islamic philanthropic institution association and the effectiveness of Islamic philanthropic institution fundraising communication. This research method is a qualitative case study type with the object of research in Islamic philanthropic institutions in Jepara, Central of Java, Indonesia. Data mining uses observation, documentation, in-depth interviews and Forum Group Discussion (FGD) techniques. The results showed that the fundraising communication strategy carried out by Islamic philanthropic institutions used interpersonal communication, public communication, involvement of figures, involvement of donors in massive activities and advertisements. The effectiveness of communication in the fundraising of Islamic philanthropic institutions uses persuasive communication techniques, getok tular (in Java means sharing information to others by mouth) in group communities and massive advertising.